Pendidikan Karakter dan Disiplin Belajar Siswa - Nurrita, Teni (STAI Al-Aqidah Al-Hasyimiyyah, 2018)
Character education as an ikhtiar to develops character values for students that are implemented in the real life. The School as an institution that can instill good value both individually and collectively. Students have a regular way of learning, concentration, discipline and continuous. That way can improve the learning achievement is good as a good step to produce quality students. Compliance students run activities according to the rules and commitment with awareness with full responsibility is the function of education. The discipline of learning will encourage students to study earnestly so that schools can develop good rules of procedure. Leadership of principals and teachers have to create as well as conditions for students to be the responsibility of all the citizens of the school.